ECONOMIC BASE ANALYSIS OF WATER, ENERGY, AND FOOD RELATED SECTORS: A CASE OF WEST JAVA PROVINCE - Purwanto, Aries (CREATIVE RESEARCH JOURNAL, 2017)
Water, energy, and food are crucial sectors to be developed due to their importance for human life. The availability, accessibility, and quality of those three commodities have to be ensured for the whole people in a region. This research was conducted to evaluate the existence of water, energy and food-related sectors compare with other sectors in West Java Province by using one of economic base approaches so-called Location Quotient (LQ) method. By analyzing gross regional domestic products (GRDP) year 2011-2015 at constant 2010 market prices by industrial origin, basic and non-basic sectors have been determined. The results show that the static and dynamic location quotient (SLQ & DLQ) analysis and competitive cluster chart were effective to figure out general situation and characteristic of basic and non-basic sectors in this region. Additionally, water, energy, and food-related sectors are mostly positioned in quadrant III and IV, indicating that serious actions have to be taken particularly by local government to increase production of those basic commodities. Integrated measures are expected to maintain their availability in the forthcoming years. This composite approach is expected to assist local government and stakeholders in undertaking preliminary evaluation in particular water, energy and food sectors to improve their security.